The Teaching of Academic Writing (a Case Study at Kresna English Course Pare) - Urmila Arini - Agus Amroni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2020)
The aim of this study to describe the teaching process of academic writing at Kresna English Course, the students‟ response toward the teaching of academic writing, and the tutor‟s solution for the problems faced by students. To collect data from the field the researcher used interview, observation, documentation, and questionnaire. The result of this study showed that the teaching process of academic writing program at Kresna English Course had been supported by handbook. The material was taken from Gramedia‟s book, the media used were whiteboard and marker, the method used was direct or natural method, the technique used was tutorial (one to one technique), and the evaluation was carried out on Friday the second week. The students had problem in constructing idea and developing writing in English. These problems increase their motivation to follow this program because it gives them a clear picture of how to define a key idea and then develop it. From student problems, tutors provide solutions by giving them tutorial (one-to-one teaching techniques) and discussions to improve their understanding of writing.